Using spontaneous fermentation sourdough in the production of rye-wheat bread with the adding amaranth flakes - Parkhomets, Iryna; Sylchuk, Tetiana (My University, 2023)
Показано використання нетрадиційної рослинної сировини для виробництва житньо-пшеничного хліба. Це дає можливість збагатити готову продукцію необхідними нутрієнтами, незамінними амінокислотами, харчовими волокнами та вітамінами

The use of non-traditional plant raw materials for the production of rye-wheat bread is shown. This makes it possible to enrich finished products with necessary nutrients, essential amino acids, dietary fibers and vitamins
Keywords: хліб; технології; борошно; якість; заклади ресторанного господарства; bread; technology; flour; quality; restaurants